Influence Innovation Agrotechnology to Efficiency Production and Revenue Farmer - Harsela, Chiska Nova (Politeknik Siber Cerdika Internasional, 2024)
Growth population and needs food that continues increase push importance innovation agrotechnology in sector agriculture . In Indonesia, efficiency production and income farmer Still become challenge main , especially among​ farmer scale small . Research This aiming For analyze influence implementation technology agrotechnology to improvement efficiency production and income farmers . Research This use method quantitative with approach descriptive correlational . Data collected through questionnaire and interview of 100 farmers in West Java who have use technology like irrigation smart , soil sensors , and agricultural drones during more from One year . Research results show that implementation technology in a way significant increase efficiency production up to 25% and income farmer up to 35%, especially for farmers who use more from One type technology . However , some challenge in adoption technology like limitations costs , access , and skills technical Still become constraint for part big farmers . Findings This show that agrotechnology own potential big in increase productivity and well-being economy farmers , but support training and financing need reinforced For increase adoption technology in a way wide